Education Modernization and Social Status Change of Suku Anak Dalam (SAD) in Jambi Province - Rizky, Muhammad; Firman, Firman; Rahman, Mohd Nazri Abdul (Widyagogik, 2023)
The Anak Dalam tribe is an underdeveloped/primitive ethnic group living in Jambi province, spread across Muaro Bungo, Tebo, Merangin, Sarolangun and Batanghari. The purpose of this paper is to see and understand the development of education in the tribe. The research method used is through a qualitative approach with a library research data collection method using sinta indexed journal sources with the last 10 years of publication, and several books that researchers have as primary data in this study. The results obtained are the government issued a nine-year compulsory education policy and specifically for Suku Anak Dalam, informal education is carried out as character education, reading, writing, counting education and counseling on the importance of education. With this, it can build the social status of the Suku Anak Dalam which can be observed that they have dared to interact with the wider community, so that the Suku Anak Dalam are not classified as a disadvantaged group anymore.